2001
DOI: 10.1093/jnen/60.5.493
|View full text |Cite
|
Sign up to set email alerts
|

The Dorsal Root Ganglia in Adrenomyeloneuropathy: Neuronal Atrophy and Abnormal Mitochondria

Abstract: Adrenomyeloneuropathy (AMN), a disease of spinal cord, brain, adrenal, and testis, mostly affects men with spastic paraparesis or ataxia beginning in their second or third decade. The spinal cord displays bilateral, usually symmetrical, long tract degeneration particularly of the gracile tract in a "dying-back" pattern. The available data strongly indicate that the fundamental lesion in AMN is an axonopathy or neuronopathy. We compared lumbar dorsal root ganglia (DRG) from 3 AMN patients to 6 age-matched contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(45 citation statements)
references
References 46 publications
2
43
0
Order By: Relevance
“…Saturated long-chain (C 16:0 to C 18:0 ) fatty acids have been shown to be toxic to intestinal mitochondria (21). Most recently, lipidic intramitochondrial inclusions have been observed in atrophic neurons of dorsal root ganglia of patients with adrenomyeloneuropathy, the adult form of X-ALD (29). Lipidic inclusions may be derived from "disintegrating cristae caused by some noxious influence" (13) and have been noted in several mitochondrial disorders (reviewed in reference 29).…”
Section: Discussionmentioning
confidence: 99%
“…Saturated long-chain (C 16:0 to C 18:0 ) fatty acids have been shown to be toxic to intestinal mitochondria (21). Most recently, lipidic intramitochondrial inclusions have been observed in atrophic neurons of dorsal root ganglia of patients with adrenomyeloneuropathy, the adult form of X-ALD (29). Lipidic inclusions may be derived from "disintegrating cristae caused by some noxious influence" (13) and have been noted in several mitochondrial disorders (reviewed in reference 29).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, adrenomyeloneuropathy, caused by a defect in the peroxisomal transporter ABCD1, is postulated to be a fundamental defect in the axonal or neuronal membrane, which leads to degeneration but not to apoptotic cell death (Powers et al, 2000(Powers et al, , 2001. Also in a mouse model with ABCD1 deficiency, it was demonstrated that axonal damage occurs as first pathological event followed by myelin degeneration (Pujol et al, 2004).…”
Section: Axonal Anomaliesmentioning
confidence: 99%
“…For example, in the dorsal root ganglia of adult X-ALD patients, atrophic neurons were observed with lipidic inclusions in the mitochondria (Powers et al, 2001), and abnormal mitochondria (condensed cristae, myelinoid figures, mitochondrial dissolution) were found in the adrenal cortical cells of (presymptomatic) 12-13 month-old ABCD1-deficient mice (McGuinness et al, 2003). In addition, a defective OXPHOS could be observed in ex vivo spinal cord slices from such mice (López-Erauskin et al, 2013), and signs of ROS (e.g., increased MDE-lysine levels) in this tissue could already be demonstrated as early as 3.5 months of age (Fourcade et al, 2008).…”
Section: Very-long-chain Fatty Acidsmentioning
confidence: 99%